Comparison between only Child and Child with Siblings on Adjustment and Personality - Saloni Arora; Anu Teotia (International Journal of Indian Psychȯlogy, 2022)
A sibling relationship is likely to be the most lasting in our lives. It has an important role not only in the family life but also influences our adjustment and wellbeing in social circumstances. However, in the face of failing fertility and increases in divorce, the number of children growing up without other children in the household has increased as families have become smaller. The term adjustment refers to the degree to which an individual’s personality functions effectively in the world of people. Personality refers to the unique and relatively stable qualities that characterize a person’s responses to life situations over a period of time. The aim of the research was to compare the level of adjustment and personality in only child and child with siblings. For this purpose, a sample of 100 adolescents (50 only child and 50 sibling child) was taken. NEO-FFI and Adjustment Inventory for College students were used as tools. The results indicate that sibling child are more adjusted than only child and also there are significant differences on the dimensions of neuroticism, extraversion and openness to experiences. Since the results show that adjustment is comparatively low in only child, it indicates that being an only child is a disadvantage in itself as they are always over pampered, and given undivided love which in turn leads to some form of maladjustment in important areas of functioning. Also, since sibling child are high on neuroticism, extraversion and openness to experiences, it indicates that how having a sibling affects the overall development of an individual which have a crucial role to play in how an individual perceive and interact with others, and how open he/she is to new ideas and experiences.